Diagnostic Accuracy of Magnetic Resonance Imaging in Determining T Stage of Urothelial Carcinoma, Taking Histopathology as Gold Standard - Shumail, Hooria; Rehman, Anis Ur; Sheikh, Ammar Zahid; Shaukat, Zara; Khalil, Safa; Maryam, Ifrah (Biological and Clinical Sciences Research Journal, 2025)
Urothelial carcinoma of the urinary bladder is a common malignancy, and accurate tumor staging is critical for selecting appropriate treatment strategies. Histopathology is the gold standard for staging, but it is invasive. Magnetic resonance imaging (MRI), particularly diffusion-weighted imaging (DWI), offers a non-invasive modality with potential for high diagnostic accuracy. Objectives: To determine the diagnostic accuracy of MRI in assessing the T stage of urothelial carcinoma, using histopathology as the gold standard. Methods: A cross-sectional study conducted at the Department of Diagnostic Radiology, Shaukat Khanum Memorial Cancer Hospital & Research Center, Lahore, from 4 March to 4 June 2025. A total of 112 patients aged 25–65 years with suspected bladder carcinoma were enrolled using non-probability consecutive sampling. All patients underwent MRI with diffusion-weighted sequences, and findings were recorded for muscle invasion. Biopsy and histopathology were performed for confirmation. MRI results were compared with histopathology to calculate sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall diagnostic accuracy. Stratification by age, gender, and BMI was performed to assess potential effect modifiers. Results: Out of 112 patients, the mean age was 44.9 ± 11.9 years, with 60.7% males. MRI showed a sensitivity of 93.4%, specificity of 52.4%, PPV of 89.5%, NPV of 64.7%, and overall diagnostic accuracy of 85.7%. Stratified analysis showed consistent diagnostic performance across age groups, gender, and BMI categories. Conclusion: MRI demonstrated high sensitivity and accuracy in detecting muscle-invasive urothelial carcinoma. Despite its moderate specificity, MRI serves as a valuable non-invasive tool that complements histopathology in clinical practice.